PANCASILA SEBAGAI LANDASAN ILMU: MEMBANGUN ILMU PENGETAHUAN BERBASIS NILAI KEBANGSAAN - Purba, Apda Ananta (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Pancasila, as the foundation of the Indonesian state, plays a crucial role not only in the life of the nation but also in the development of science. This article discusses how Pancasila can serve as a moral and ethical basis for scientific development that is relevant to the social, cultural, and political context of Indonesia. A qualitative approach with descriptive analysis is employed through literature studies and interviews with experts. Pancasila, consisting of five principles, can guide the development of science that is not only technical but also oriented towards human values and social welfare. The article also highlights the importance of integrating Pancasila into higher education curricula in Indonesia to strengthen national identity and global competitiveness.